THE EXPERIENCE OF THE DAYAK PEOPLE IN HEALING ILLNESSES THROUGH THE TRADITIONAL RITUALS OF THE DAYAK NGAJU: A PHENOMENOLOGICAL STUDY - Cahayani, Erlina; Yani, Achir; Syafwani, Muhammad (Nursing Sciences Journal, 2025)
Background: The Dayak Ngaju community in Palangka Raya, continues to practice traditional healing rituals despite the availability of modern healthcare services. Preferences for rituals such as Sangiang, Nyadiri, and Balian reflect the community's strong cultural identity and belief in supernatural healing. Objective: This study aims to explore the subjective experiences of the Dayak Ngaju people in undergoing healing processes through traditional rituals. Methods: This research employed a qualitative approach with an phenomenological design. A total of 10 participants were selected using purposive sampling. Data were collected through in-depth interviews, observation, and field notes. Thematic analysis using Colaizzi’s method was applied, involving seven stages. Results: Thematic analysis revealed nine key themes: (1) cultural background and connection, (2) factors influencing the choice of ritual, (3) personal experiences with ritual healing, (4) traditional healing practices of Dayak Ngaju, (5) meaning and beliefs about rituals, (6) interaction with modern healthcare systems, (7) sociocultural influences, (8) hopes for the future of the tradition, and (9) expectations and utilization. The findings underscore the importance of integrating transcultural perspectives into nursing practice and highlight the need for culturally sensitive care, improved cultural competence among healthcare providers, and collaborative approaches between traditional healers and medical professionals within inclusive healthcare systems